The importance of being elastic: Deflection of a badminton racket during a stroke - Kwan, M.; Rasmussen, J. (Journal of Sports Sciences, 2010)
The deflection profiles of a badminton racket during strokes performed by elite and world-class badminton players were recorded by strain gauges and subsequently analysed to determine the role of shaft stiffness in racket performance. Deflection behaviour was consistent in all strokes across all players, suggesting a controlled use of racket elasticity. In addition, all impacts occurred within 100 ms of each other, a duration in which deflection velocity provides an increase in racket velocity, indicating that the players were able to use racket elasticity to their advantage. Since deflection behaviour is a product of the racket-player interaction, further work is required to determine the effects of different racket properties and player techniques on the elastic response of rackets during strokes.